Ruthenium-iridium mixed oxides RuxIr1-xO2 prepared by sol-gel method and applied to catalytic methane combustion - Khalid, Omeir; Justus Liebig University Giessen (My University, 2021)
The mechanism of the methane combustion reaction is split into an initial activation of the C H bond to form methyl (CH3) and methylene (CH2), followed by either a direct oxidation to CO2 or alternatively to the formation of CO and H2 via the formaldehyde route first. This work presents ruthenium-iridium mixed oxides (RuxIr1-xO2) applied to methane combustion for the first time. The high activity of ruthenium during catalytic oxidation reactions and the ability of iridium to activate the C-H bond at low temperatures are combined to form promising materials. The Pechini sol-gel method allows to prepare the rutile ruthenium-iridium mixed oxides (RuxIr1 xO2) with high compositional and structural control throughout the whole composition range x. In addition, a slightly modified route enables the preparation of supported ruthenium-iridium mixed oxides (RuxIr1-xO2@TiO2) in order to increase the noble metal utilization for catalytic purposes. With X-ray diffraction and X-ray photoelectron spectroscopy a core-shell-like structure has been revealed. The metallic core shows a miscibility gap in the composition range x=0.21 and x=0.74 forming fcc-Ru0.21Ir0.79 and hcp-Ru0.74Ir0.26, as confirmed by Rietveld refinement. The overgrown oxide, unlike the metallic core, shows no segregation throughout the entire composition range, shown by systematic composition-dependent shifts for the rutile (101) reflection spot (XRD) and O 1s binding energy (XPS) for the various compositions, indicating the successful formation of solid solutions. Raman spectroscopy underpins the successful formation of oxide solid solutions by showing a continuous shift in the wavenumbers of the Raman active modes according to the ruthenium (iridium) content. The number of accessible surface noble metal atoms in the supported materials (RuxIr1 xO2@TiO2), measured via CO chemisorption experiments, determine the relative active surface areas, which are required for proper normalization of the catalytic activities in terms of space-time-yield. Additional XPS studies confirm high dispersion of the active component on the TiO2 support by revealing high relative surface noble metal concentrations, three to five times higher than as expected from the nominal loading (5 mol%). This indicates the high amount of interface between support and active component, which is mandatory for a good combustion catalyst to show thermal stability and hinder sintering, for instance. Catalytic activity tests of the unsupported RuxIr1 xO2 catalysts are conducted with the prototypical CO oxidation reaction under oxidizing and under stoichiometric reaction conditions. The metallic core is buried and does therefore not contribute to the activity. IrO2 is the least active of the presented materials. Surprisingly, not the pure RuO2 but the Ru0.875Ir0.125O2 has proven itself as the best catalyst validating the harmonious and synergistic interplay of both noble metals. All RuxIr1 xO2 catalysts are bulk-stable under the reaction conditions considered. However, upon CO oxidation reaction the Ir4+ concentration at the mixed oxide surface is significantly enhanced with respect to its bulk composition. Catalytic and kinetic data for the methane combustion over both unsupported RuxIr1-xO2 and supported RuxIr1-xO2@TiO2 catalysts with varying compositions x are presented. In absolute contrast to the CO oxidation reaction, pure RuO2 is the least active catalyst for methane combustion. However, not the analogue counterpart, pure IrO2, but Ru0.25Ir0.75O2 showed the highest intrinsic activity. The same trend can be observed for the supported materials (@TiO2), where Ru0.25Ir0.75O2@TiO2 is the most active material. Surprisingly, even Ru0.75Ir0.25O2 and Ru0.75Ir0.25O2@TiO2 are remarkably active in methane combustion, indicating that little iridium in the mixed RuxIr1-xO2 oxide component improves the activity of the methane combustion considerably. Recalling the results from both CO oxidation and methane combustion, the C-H activation is rate limiting in methane combustion rather than the further oxidation to CO and CO2. Additional reaction order experiments underline this statement by revealing a reaction order of zero for O2 and a reaction order of one for CH4, implying that the reaction rate correlates with the superficial population of methane molecules while the dissociative adsorption and supply of oxygen at the active site for further oxidation are not hampered. The relatively inferior performance of pure RuO2 during methane combustion obviously shows that iridium is important for the initial activation of methane but the admixture of ruthenium is mandatory to guarantee efficient oxidation of the methyl and methylene to form CO2. Thus, accompanied by synergistic effects, the ruthenium-iridium mixed oxides are uncovered as promising candidates, which can compete with the Pd-based benchmark catalysts as concluded from direct comparison of T50 and T90 values, where the conversion is 50% and 90% respectively. Especially the Ru0.75Ir0.25O2@TiO2, with a slightly lower intrinsic activity compared to pure IrO2@TiO2 but much higher amount of the more abundant ruthenium turns out to be most interesting for further methane combustion studies.
Keywords: Ruthenium; Iridium; Mixed Oxides; Methane Combustion; ddc:540